Memorandum of Understanding between the Department for International Development and BRAC University for Increasing safe births through developing community midwives in Bangladesh (2012) - Department for International Development, UKaid; James P. Grant School of Public Health, BRAC University (Department for International Development and BRAC University, 2013)
Accountable grant arrangement for "Increasing safe births through developing community midwives in Bangladesh" between Department for International Development and BRAC University.